Pathway sensitivity analysis for detecting pro-proliferation activities of oncogenes and tumor suppressors of epidermal growth factor receptor- extracellular signal-regulated protein kinase pathway at altered protein levels - Li, H. (2014)
10.1002/cncr.24485